Ischemic colitis caused increased early and delayed mortality - Gilshtein, Hayim (World J Emerg Surg, 2018)
BACKGROUND: Ischemic colitis remains a challenge for the surgeon, both in its diagnosis and treatment. Data from a single tertiary center, of patients diagnosed with ischemic colitis, was collected. An attempt was made to delineate the patients requiring surgical intervention. METHODS: A retrospective study was undertaken in patients diagnosed with ischemic colitis admitted to Rambam Health Care Campus between 2011 and 2016. The primary outcome was defined as mortality. Secondary outcomes were defined as complications during conservative treatment and postoperative course. RESULTS: Sixty-three patients were diagnosed with ischemic colitis during the study period. The mean age at presentation was 72.5 years, with a female predominance (62%). The overall mortality rate was 29% (18/63). Six patients (50%) of those operated died. An older age, comorbidities and higher lactate levels present risk factors for a worse outcome. CONCLUSIONS: Ischemic colitis continues to present a challenge in its management. A better understanding of the disease process is required. And one needs to adhere to sound surgical principles for a timely diagnosis and treatment, especially in older patients with worrisome clinical, laboratory, and imaging features.